Duel at Low Hawk - West, Charles (New York : Berkley, 2022)
"Boot Stoner spent twelve years of his life behind bars for stealing horses and rustling cattle. Upon release, he added murder and kidnapping to his criminal skills-- slaughtering his own parents and abducting his "sister," a young Creek girl that his folks had adopted--before exacting revenge against the man responsible for his incarceration. U.S. Deputy Marshal John Ward is one of the Wests best manhunters. Hes the only one who stands a chance of stopping Stoners bloody rampage--and of bringing the girl back alive...."--Back cover.
Keywords: Ex-convicts -- Fiction; Revenge -- Fiction; Kidnapping -- Fiction; Parricide -- Fiction; Frontier and pioneer life -- Fiction; Western fiction; Historical fiction